2011
DOI: 10.1021/bi1006332
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Multiple Folding Pathways of Monellin Using Pulsed Thiol Labeling and Mass Spectrometry

Abstract: Protein folding reactions often display multiexponential kinetics of changes in intrinsic optical signals, as a manifestation of heterogeneity, either on one folding pathway or on multiple folding pathways. Delineating the origin of this heterogeneity is difficult because different coexisting structural forms of a protein cannot be easily distinguished by optical probes. In this study, the complex folding reaction of single-chain monellin has been investigated using a pulsed thiol labeling (SX) methodology in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 28 publications
(49 citation statements)
references
References 61 publications
2
47
0
Order By: Relevance
“…MMTS-labeling experiments were performed as described previously (33,35). In brief, RNase H was unfolded in 3.4 M GdmCl inside a quenched-flow machine (SFM-400 Q/S from Biologic), and a 6-ms pulse of 20 mM MMTS was applied at different times of unfolding.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MMTS-labeling experiments were performed as described previously (33,35). In brief, RNase H was unfolded in 3.4 M GdmCl inside a quenched-flow machine (SFM-400 Q/S from Biologic), and a 6-ms pulse of 20 mM MMTS was applied at different times of unfolding.…”
Section: Methodsmentioning
confidence: 99%
“…1A). We used two different thiol-specific labeling reagents, 5,5′-dithiobis (2-nitrobenzoic acid) (DTNB) and methyl metahnethiosulfonate (MMTS), both of which react rapidly with exposed thiolate groups (33)(34)(35), to measure the changes in solvent accessibility during unfolding ( Fig. 5 A−C).…”
Section: Initial Expansion Is Not Accompanied By Disruption Of Secondarymentioning
confidence: 99%
“…Nevertheless, and not surprisingly perhaps, it has been shown that the fast phase seen in the folding of scMN also leads to the formation of two intermediates of differing stabilities on two competing pathways. 7,42 Kinetic model for the folding of dcMN A global fitting program, written in MATLAB, was used to quantitatively analyze the dependence of the refolding kinetics on GdnHCl concentration, according to Scheme 3. Details about the fitting program are provided in Materials and Methods.…”
Section: Upwardly Curved Chevrons Are Indicative Of Multiple Folding mentioning
confidence: 99%
“…2,3 Multiple pathways have indeed been observed to operate during the folding and unfolding of several proteins. [4][5][6][7][8][9][10][11][12] Much is yet to be learnt about how competing folding pathways differ in the sequence of structural events defined by each pathway, as well as about the nature of the free energy barriers on a folding pathway. 13,14 Multiple folding pathways are associated with structural heterogeneity in the unfolded state [15][16][17][18] and intermediates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation